High-velocity micro-particle impact on gelatin and synthetic hydrogel. (October 2018) - Veysset, David; Kooi, Steven E.; Мaznev, A.A.; Tang, Shengchang; Mijailovic, Aleksandar S.; Yang, Yun Jung; Geiser, Kyle; Van Vliet, Krystyn J.; Olsen, Bradley D.; Nelson, Keith. A.
Abstract: The high-velocity impact response of gelatin and synthetic hydrogel samples is investigated using a laser-based microballistic platform for launching and imaging supersonic micro-particles. The micro-particles are monitored during impact and penetration into the gels using a high-speed multi-frame camera that can record up to 16 images with nanosecond time resolution. The trajectories are compared with a Poncelet model for particle penetration, demonstrating good agreement between experiments and the model for impact in gelatin. The model is further validated on a synthetic hydrogel and the applicability of the results is discussed. We find the strength resistance parameter in the Poncelet model to be two orders of magnitude higher than in macroscopic experiments at comparable impact velocities. The results open prospects for testing high-rate behavior of soft materials on the microscale and for guiding the design of drug delivery methods using accelerated microparticles.